Investigation of the Optical Properties of the Achromatic Quadrupole Lens by Using the Rectangular Potential Distribution Model (Baghdad Science Journal, 2009)
An optimization calculation is made to find the optimum properties of combined quadrupole lens which consists of electrostatic and magnetic lens. Both chromatic and spherical aberration coefficients are reduced to minimum values and the achromatic aberration is found for many cases. These calculations are achieved with the aid of transfer matrices method and using rectangular model of field distribution, where the path of charged-particles beam traversing the field has been determined by solving the trajectory equation of motion and then the optical properties for lens have been computed with the aid of the beam trajectory along the lens axis. The computations have been concentrated on determining the chromatic and spherical aberration coefficients in both convergence and divergence planes and the effects of changing both of excitation and effective length of lens are studied.